Potential of probiotic strains as basis of food supplement for managing cardiovascular health: a focus on hypocholesterolemic activity and prevention of high cholesterol-related conditions - Starovoitova, Svitlana; Demchenko, Olga; Kishko, Karina; Spivak, Mykola (My University, 2024)
The obtained results allow us to assert that it is necessary to develop a line of food supplements and probiotics, based on the studied strains and their compositions in encapsulated form (which will increase the survival of probiotic microorganisms when passing through the upper gastrointestinal tract, which will indirectly increase the therapeutic effect of such drugs and products) , for prevention and treatment of diseases associated with the negative manifestations of high cholesterol levels. Probiotics that contain cholesterol-assimilating strains can efficiently complete the complex therapy of CVD, cancer etc

Отримані результати дозволяють стверджувати про необхідність розробки лінійки харчових добавок та пробіотиків на основі досліджуваних штамів та їх композицій у капсульованому вигляді (що дозволить підвищити виживаність пробіотичних мікроорганізмів при проходженні через верхні відділи шлунково-кишкового тракту, що опосередковано підвищить терапевтичний ефект таких препаратів і продуктів), для профілактики та лікування захворювань, пов’язаних з негативними проявами високого рівня холестерину. Пробіотики, до складу яких входять штами, що асимілюють холестерин, можуть ефективно завершувати комплексну терапію ССЗ, онкологічних захворювань тощо
Keywords: probiotic strains; hypocholesterolemic activity; food supplement; cardiovascular diseases; пробіотичні штами; гіпохолестеринемічна активність; фукнціональні продукти харчування; серцево-судинні захворювання; кафедра біотехнології і мікробіології